CONHECIMENTO DE MÉDICOS E ENFERMEIROS ATUANTES NO PRÉ-NATAL SOBRE TOXOPLASMOSE - Ana Dorcas de Melo Inagaki; Isla Evellen Santos Souza; Anne Caroline Lima Araujo; Ana Cristina Freire Abud; Nadyege Pereira Cardoso; Caique Jordan Nunes Ribeiro (Universidade Federal do Paraná, 2020)
Objectives: To describe the knowledge of doctors and nurses who provide prenatal care about toxoplasmosis. Method: Cross-sectional analytical study, conducted between October 2018 and February 2019, with 89 professionals from 43 Basic Health Units in Aracaju, State of Sergipe, in Brazil, through a self-administered questionnaire. Absolute and relative frequencies and odds ratios were calculated. Fischer Exact test and Chi-square test were used for data analysis. Results: Doctors and nurses who provide prenatal care have shown little knowledge about toxoplasmosis related to infectious forms (p = 1,000), transmission routes (p = 1,000), vulnerable group (p = 0,290), transmission period (p = 1,000), greater risk for complications in newborns (p = 0.828), when tests should be performed (p = 0.015), indication for performing and interpretation of the avidity test (p = 0.355). Conclusion: The present study identified knowledge gaps and may contribute to planning continuing education for prenatal care professionals, in order to prevent congenital toxoplasmosis.